Body, Land, and Oppression: An Ecofeminist Analysis of Nawal El-Saadawi’s Al-Ughniyyat Al-Daairiyah - Farhan Hardiansyah; Dayudin Dayudin; Khomisah Khomisah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study examines the problem of patriarchal domination and the intertwined oppression of women and nature in Nawal El-Saadawi’s novel Al-Ughniyyat Al-Daairiyah. It aims to identify the forms of patriarchal control depicted in the narrative, uncover the meanings of bodily and spatial colonization experienced by the female characters, and analyze the relationship between women and nature from an ecofeminist perspective. The research employs a descriptive qualitative method using close reading and note-taking techniques. The primary data source is the text of the novel itself, which is analyzed through ecofeminist theories proposed by Karen J. Warren and Vandana Shiva. The findings reveal that the female body is represented as a political and ideological space subject to regulation and domination, paralleling the patriarchal exploitation of nature. Acts of bodily colonization, institutional violence, and symbolic links between the body and the environment illustrate a persistent logic of domination embedded in social structures. The novel ultimately asserts that the struggle for women’s emancipation is inseparable from the restoration of ecological balance. This research contributes to contemporary Arabic literary criticism by offering an integrated ecofeminist reading and enriching interdisciplinary discussions on gender, power, and environmental ethics in modern Arabic literature.